Thoracic Surgical Techniques - Wells, Francis C. (Springer International Publishing, 2018)
This heavily revised second edition of this book provides a comprehensive overview of both common and rarely performed thoracic surgical techniques. Techniques covered include thymectomy, left and right lower lobectomy, rib resection for empyema, median sternotomy and lung biopsies. Emphasis is focused on the practical steps necessary to successfully and reliably perform the techniques covered, while acknowledgement is also given to individual variations in how these techniques are performed. Thoracic Surgical Techniques provides a detailed clinical illustrative guide for successfully performing a range of procedures reliably. Its large number of detailed illustrations and concise technical descriptions provides an invaluable resource for all practising and trainee thoracic surgeons.